Automatic speed control system for the chemical etching of thin films - Dalekorej, A.V.; Ivanytsky, V.P.; Kryuchyn, A.A.; Legeta, Ya.P.; Petrov, V.V.; Rubish, V.M.; Ryaboshchuk, M.M.; Chychura, I.I. (Physics and Chemistry of Solid State, 2025)
The possibility of creating automatic control systems based on the interferometric optical method for chemical etching processes has been shown. A structural diagram of device for automatic control of the construction of an optical path from the elements of modern information fiber-optic systems has been developed. An experimental model of an automatic control system with optimal spectral "binding" of the radiation source, optical fibers, Y-splitter and photodetector has been created. The results of experimental studies of changes in the interference during chemical etching of thin films have shown that the created model provides simplicity of optical adjustment, high noise immunity and simplicity of automation of control of the entire etching process. Based on the results which were obtained during the study of the experimental model, a basic algorithm for the functioning of automatic control systems for chemical etching processes using the interferometric optical method has been developed.